Thermal And Flow Characterization Of Nanofluid-Based Cooling Systems For High-Performance Mechanical Applications - Merin Selva Andela (Journal of Advanced Engineering and Technology Research, 2025)
Nanofluids, engineered suspensions of nanoparticles in base fluids, have emerged as a promising solution for enhancing thermal management in high-performance mechanical systems. This study investigates the thermal and flow characteristics of Al₂O₃-water and CuO-water nanofluid-based cooling systems using both experimental measurements and computational fluid dynamics (CFD) simulations. The effects of nanoparticle concentration, flow rate, and hybrid formulations on convective heat transfer and pressure drop were evaluated. Results indicated that nanofluids significantly improve heat transfer performance, with enhancements up to 28% compared to conventional fluids, while maintaining manageable viscosity levels. Hybrid nanofluids further enhanced thermal performance by leveraging complementary nanoparticle properties. CFD results validated experimental findings, providing detailed insight into nanoparticle transport and local temperature distribution. The study demonstrates that optimized nanofluid-based cooling systems can effectively manage high heat fluxes, offering a practical approach for reliable and efficient thermal management in advanced mechanical applications.